Pyrolysis of furniture wood waste: Decomposition and gases evolved - Moreno, Ana Isabel; Font, Rafael (Journal of analytical and applied pyrolysis, 2015)
•Pyrolysis of furniture wood waste.•Kinetic parameters of pyrolysis from TG analysis.•Analysis of gas, volatile and semi-volatile products evolved. The pyrolysis of furniture wood waste was studied due to its importance as a thermochemical conversion process, and also because it is a step in the combustion process. Furniture wood contains organic additives and inorganic elements (being noteworthy the high content of Ti). These additives cause changes in the thermal processes. A thermogravimetric analysis of the pyrolysis of furniture wood waste was carried out in a TGA apparatus using dynamic and dynamic+isothermal runs. The pyrolysis was modeled with acceptable approximation by three independent reactions, according to the decomposition of the main components of the wood (hemicellulose, cellulose and lignin). The gaseous products evolved during the pyrolysis were measured by the TG-MS and TG-FTIR techniques. The maximum formation of gases occurs around 360°C. The CO2 formation remains until the end of the run, due to the wide range of lignin degradation. In addition, runs to identify the volatile and semi-volatile compounds were also carried out in a laboratory scale tubular reactor at 500 and 850°C and the results were compared with the pyrolysis of a cleaner wood.